A long-term cohort study: the immune evasion and decreasing neutralization dominated the SARS-CoV-2 breakthrough infection - Liu, Qianyun; Jin, Meihua; Mei, Fanghua; Fan, Hui; Gu, Mengxue; Zhang, Yuzhen; Qian, Shengnan; Tan, Xue; Ji, Lei; Zhang, Zhen; Chen, Guozhong; Yan, Huan; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Most of vaccinees and COVID-19 convalescents can build effective anti-SARS-CoV-2 humoral immunity, which helps preventing infection and alleviating symptoms. However, breakthrough viral infections caused by emerging SARS-CoV-2 variants, especially Omicron subvariants, still poses a serious threat to global health. By monitoring the viral infections and the sera neutralization ability of a long-tracked cohort, we found out that the immune evasion of emerging Omicron subvariants and the decreasing neutralization led to the mini-wave of SARS-CoV-2 breakthrough infections. Meanwhile, no significant difference had been found in the infectivity of tested SARS-CoV-2 variants, even though the affinity between hACE2 and RBDs of tested variants showed an increasing trend. Notably, the immune imprinting of inactivated COVID-19 vaccine can be relieved by infections of BA.5.2 and XBB.1.5 variants sequentially. Our data reveals the rising reinfection risk of immune evasion variants like Omicron JN.1 in China, and suggesting the importance of booster with updated vaccines.